2010 IEEE International Conference on Automation, Quality and Testing, Robotics (AQTR) 2010
DOI: 10.1109/aqtr.2010.5520898
|View full text |Cite
|
Sign up to set email alerts
|

Feedback linearization control design for the 13C cryogenic separation column

Abstract: The separation of carbon isotopes represents a major research area due to the numerous uses of the least abundant carbon isotope, 13 C. One of the methods used for separating these isotopes is the cryogenic distillation, in large counter-current columns. Such industrial plants represent a difficult problem in terms of automatic control, since they are characterized by nonlinearities, large delay times and extremely severe control input constraints. The paper presents a control strategy based on a feedback line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The feedback linearization method can be extended to the nonlinear MIMO square systems (Sastry, 1999). As mentioned earlier, to overcome the disadvantages of classical feedback linearization, the robust feedback linearization can be applied as well (Franco et al, 2006; Pop and Dulf, 2010; Pop et al, 2010).…”
Section: Problem Formulation and Designmentioning
confidence: 99%
“…The feedback linearization method can be extended to the nonlinear MIMO square systems (Sastry, 1999). As mentioned earlier, to overcome the disadvantages of classical feedback linearization, the robust feedback linearization can be applied as well (Franco et al, 2006; Pop and Dulf, 2010; Pop et al, 2010).…”
Section: Problem Formulation and Designmentioning
confidence: 99%
“…The robust feedback linearization approach where the linearized system would be equal to the tangent linearized system around the chosen operating point causes only a small transformation in the natural behaviour of the original system and the robust linear controller will maintain the robustness properties when applied for uncertain nonlinear systems (Franco et al, 2006;Guillard and Bourles, 2000;Pop et al, 2010). In the works of Glover (1990, 1992), the authors have suggested to combine the loop shaping technique and the H ' robust stabilization approach in order to develop the Loop Shaping Design Procedure (LSDP) approach.…”
Section: Introductionmentioning
confidence: 99%
“…The robust feedback linearization approach (Franco et al, 2006;Guillard and Bourles, 2000;Pop et al, 2010) where the linearized system would be equal to the tangent linearized system around the chosen operating point causes only a small transformation in the natural behaviour of the original system in such a way that the robust linear controller will maintain the robustness properties when applied for uncertain nonlinear systems.…”
Section: Introductionmentioning
confidence: 99%